2011
DOI: 10.3390/molecules16021710
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and Their Isomers: Color Pigments in Fruits and Vegetables

Abstract: Fruits and vegetables are colorful pigment-containing food sources. Owing to their nutritional benefits and phytochemicals, they are considered as 'functional food ingredients'. Carotenoids are some of the most vital colored phytochemicals, occurring as all-trans and cis-isomers, and accounting for the brilliant colors of a variety of fruits and vegetables. Carotenoids extensively studied in this regard include β-carotene, lycopene, lutein and zeaxanthin. Coloration of fruits and vegetables depends on their gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
289
1
13

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 473 publications
(314 citation statements)
references
References 110 publications
11
289
1
13
Order By: Relevance
“…However, the carotenoid contents did not differ significantly. These small losses could be attributed to the low solubility of carotenoids in aqueous solutions (Khoo et al, 2011). In contrast, Araya-Farias et al (2014) observed significant losses in carotenoids during sea buckthorn (Hippophae rhamnoides L.) OD, which might be related to the higher OD time employed by the authors, of 6 hours.…”
Section: Resultscontrasting
confidence: 41%
“…However, the carotenoid contents did not differ significantly. These small losses could be attributed to the low solubility of carotenoids in aqueous solutions (Khoo et al, 2011). In contrast, Araya-Farias et al (2014) observed significant losses in carotenoids during sea buckthorn (Hippophae rhamnoides L.) OD, which might be related to the higher OD time employed by the authors, of 6 hours.…”
Section: Resultscontrasting
confidence: 41%
“…In the particular case of kiwifruit (Actinida deliciosa), a comparatively caloric (57 59 kcal/100g) and nutritious fruit rich in vitamin C, potassium, folate and fibre (Drummond, chlorophyllides and pheophorbides (Cano & Marín 1992), and cis-trans isomerization of 76 carotenoids and formation of epoxides, furanoids and other degradation products of these 77 compounds (Khoo et al, 2011). Accordingly, the typical bright green colour turns to a 78 yellowish-brown tone (Cano & Marín, 1992), and a product with an appearance very 79 different from that of the raw kiwifruit is obtained (Cano, 1991).…”
mentioning
confidence: 99%
“…3.1 Analysis of lutein and other carotenoids in mugwort paste It is well known that the major carotenoids in vegetables and fruits are xanthophylls lutein, zeaxanthin, and β-cryptoxanthin and hydrocarbon carotenoids α-carotene, β-carotene, and lycopene 14 . In this study, we focused on these carotenoids especially lutein because their presence was assumed in mugwort.…”
Section: Resultsmentioning
confidence: 99%